Surface spectroscopic and molecular beam studies of the reactions of trimethylaluminium on Si(100) - Wee, A; Jackman, R; Price, R; Foord, J (1989)
The reactions of trimethylaluminium leading to the deposition of Al on Si have been studied using LEED, XPS, AES, TDS and molecular beam scattering. Trimethylaluminium is shown to chemisorb on Si(100) subsequently decomposing to produce CH4(g) and contaminated Al layers. Al catalyses the decomposition reaction and opens up a new reaction channel, resulting in the evolution of C2H2(g).